UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN COOPERATIVE LEARNING MODEL JIGSAW DI SMP NEGERI 1 KIBIN - Sujai, Ahmad (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
The purpose of this study is to improve student activity and learning outcomes towards the basic concepts and competencies of the lesson through Cooperative Learning Jigsaw, about the law of mad reading in grade 8. The method used in this study is a qualitative method. The subject of the study was a grade 8.E student To carry out the learning above, is to use the Cooperative Learning Model Jigsaw. Through jigsaw model learning, it is hoped that "Active, Creative, Effective and Fun Learning (PAKEM)" will be created, especially in this subject. Because there are problems in learning outcomes that are still under KKM, the correctness of the class action hypothesis needs to be supported by accurate data and information obtained through research. The data in this study was obtained from learning outcomes tests carried out each cycle as well as data from teacher observation sheets and student questionnaires. Based on the results of research and data analysis, observation and interviews, the average grade point and level of mastery of material above SKBM (70%) in Islamic Religious Education subjects have increased. The average results of gains ranging from Pre-Cycle, Cycle 1 and Cycle 2, among others; Pre-Cycle was 69.68, Cycle 1 was 73.75, and Cycle 2 was 77.80. The number of students who were able to master the material above SKBM at the end of cycle 2 was 29 people from the number of students in class VIII.E or 85.00%. Teacher activities in the teaching and learning process have improved, this can be seen from the average score obtained by teachers in cycle 1 is 86.67% while in cycle 2 to 98.33%, there is a significant increase from good to very good grades. The increase was obtained from several activities, namely the origin of 75.00%, then in learning activities with the Jigsaw model to 100%. In the activity of giving awards to students, there was a slight increase, from 75.00% to 87.50%, in apperception activities of 93.75%.